Aplikasi Remote Sensing dan Geographic Information System untuk Pemetaan Komoditas Unggulan di Kabupaten Badung - IRNAWATI IRNAWATI; I KETUT SARDIANA; INDAYATI LANYA (Agrotrop : Journal on Agriculture Science, 2019)
Applications Remote Sensing and Geographic Information System for Mapping of Superior Commodities in Badung District. Superior commodity is one of the conditions in the development of agricultural areas included in (Regulation of the Minister of Agriculture No. 56 of 2016). As for the development of food crops agriculture is based on land suitability classes found in technical guidelines (Ministry of Agriculture, 2017). The two regulations require that each Province develop a master plan for developing agricultural commodities, which is based on superior commodities and land suitability classes. Quantitative and qualitative methods include: (1) identification and interpretation of land use using satellite imagery, (2) field surveys, (3) re-interpretation of satellite images, (4) Location Quotient (LQ) analysis for competitive superior commodities and Shift Share Analysis (SSA) for comparative advantage, (5) Mapping of superior commodities and land suitability of food crops. The use of paddy fields in Badung Regency is 9069.11 ha, moor (898,797 ha), and mixed gardens (3898,615 ha). Competitive superior commodities (LQ) for: (1) paddy rice, located in Abiansemal, Mengwi, North Kuta and Kuta Districts, (2) corn, peanuts, sweet potatoes and cassava in Petang District, (3) soybeans and green beans in Mengwi District. Comparative superior commodities (SSA) of paddy rice are found in the Districts of Petang and Mengwi. While sweet potatoes in Abiansemal District and cassava in Petang District. Potential agroecosystem suitability classes for food crops and secondary crops in the study area are generally classified as very suitable (S1) except in the Petang District which is quite suitable (S2-t, rc1) with a low temperature limiting factor and a rough texture. Increasing the suitability class of paddy and palawija requires fertilizing and adding organic materials to increase production.